Analysis of Typhoon-Induced Wave Overtopping Vulnerability Due to Sea Level Rise Using a Coastal–Seawall–Terrestrial Seamless Grid System - Seung-Won Suh; Myeong-Hee Lee (Journal of Marine Science and Engineering, 2023)
The vulnerability to coastal disasters resulting from storm surges and wave overtopping (WOT) during typhoon intrusions is significantly escalating due to rising sea levels. In particular, coastal seawalls constructed along the coast through engineered assessments are experiencing an increase in the frequency of WOT and associated flooding in proportion to the reduction in freeboard due to rising sea levels. This study employed a unified modeling system that combines an empirical formula for estimating WOT volumes with a numerical model simulating tides, waves, and storm surges. The analysis was conducted across the Northwest Pacific (NWP) Ocean, encompassing coastal seawalls and terrestrial regions, using an integrated seamless grid system, which utilized ADCIRC + SWAN + EurOtop, for the present day, 2050, 2070, and 2100 to investigate how vulnerability to WOT changes with sea level rise. The maximum envelope of WOT inundation results for three historical and two 100-year return period synthetic typhoons confirms that vulnerability to WOT intensifies with rising sea levels. The single-process integrated model applied in this study can serve not only for long-term coastal seawall protection design but also for the short-term early warning system for storm surges and WOT, contributing to immediate preparedness efforts.